Modeling of an Electric Vehicle with MATLAB/Simulink - Hamit Solmaz; Ahmet Onur Kıyaklı (International Journal of Automotive Science and Technology, 2018)
Conventional vehicles utilize petroleum derived fuels to provide good per-formance and long range. But there are some disadvantages such as low fuel economy and exhaust gas emissions causing environmental pollution. In this re-spect, interest in electric vehicles is increasing. In this study, the dynamic model of an electric vehicle was created with MATLAB/Simulink. The energy con-sumption values of the electric vehicle were determined. The effect of parame-ters on vehicle performance and energy consumption has been examined. As a result of tests, the vehicle consumes 15.82 kWh of energy per 100 kilometers and the vehicle has a 177 kilometers range, according to NEDC. With regenera-tive braking, an energy saving of 8% was achieved in 100 kilometers.